2022
DOI: 10.7554/elife.80555
|View full text |Cite
|
Sign up to set email alerts
|

Channel-independent function of UNC-9/Innexin in spatial arrangement of GABAergic synapses in C. elegans

Abstract: Precise synaptic connection of neurons with their targets is essential for the proper functioning of the nervous system. A plethora of signaling pathways act in concert to mediate the precise spatial arrangement of synaptic connections. Here we show a novel role for a gap junction protein in controlling tiled synaptic arrangement in the GABAergic motor neurons in Caenorhabditis elegans, in which their axons and synapses overlap minimally with their neighboring neurons within the same class. We found that while… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 92 publications
0
7
0
Order By: Relevance
“…This is strengthened by evidence of gap junctions in ultrastructural EM-based analyses in both invertebrates ( Cook et al, 2019 ; Jarrell et al, 2012 ; White et al, 1986 ) and vertebrates ( Smedowski et al, 2020 ; Anderson et al, 2011 ), as well as expression studies showing cell type- and tissue-specific spatial patterns of innexin and connexin genes ( Bhattacharya et al, 2019 ). In addition, studies involving perturbations of innexins and connexins have shown diverse contributions of electrical synapses to neuronal function ( Hendi et al, 2022 ; Bhattacharya et al, 2019 ; Hall, 2017 ; Song et al, 2016 ; Meng et al, 2016 ; Kawano et al, 2011 ; Bloomfield and Völgyi, 2009 ; Yeh et al, 2009 ; Chuang et al, 2007 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is strengthened by evidence of gap junctions in ultrastructural EM-based analyses in both invertebrates ( Cook et al, 2019 ; Jarrell et al, 2012 ; White et al, 1986 ) and vertebrates ( Smedowski et al, 2020 ; Anderson et al, 2011 ), as well as expression studies showing cell type- and tissue-specific spatial patterns of innexin and connexin genes ( Bhattacharya et al, 2019 ). In addition, studies involving perturbations of innexins and connexins have shown diverse contributions of electrical synapses to neuronal function ( Hendi et al, 2022 ; Bhattacharya et al, 2019 ; Hall, 2017 ; Song et al, 2016 ; Meng et al, 2016 ; Kawano et al, 2011 ; Bloomfield and Völgyi, 2009 ; Yeh et al, 2009 ; Chuang et al, 2007 ).…”
Section: Resultsmentioning
confidence: 99%
“…For chemical synapses, these include reporters labeling pre- and post-synaptic proteins – such as SNB-1/VAMP, RAB-3, SYD-2/Liprin, CLA-1/Piccolo, and GLR-1/AMPAR – fused with a fluorescent protein ( Xuan et al, 2017 ; Mahoney et al, 2006 ; Yeh et al, 2005 ; Shen and Bargmann, 2003 ; Zhen and Jin, 1999 ; Nonet, 1999 ; Rongo et al, 1998 ; Jorgensen et al, 1995 ) and split-fluorophore transsynaptic technology such as GFP Reconstitution Across Synaptic Partners (GRASP) ( Feinberg et al, 2008 ) and other variants ( Feng et al, 2020 ; Feng et al, 2019 ), and Biotin Labeling of Intercellular Contacts (iBLINC) ( Desbois et al, 2015 ; Figure 1A ). In the case of electrical synapses, innexins can be endogenously tagged with fluorescent proteins to visualize homo- or heteromeric electrical synapses ( Hendi et al, 2022 ; Gordon et al, 2020 ; Bhattacharya et al, 2019 ; Figure 1A ). These tools have been somewhat constrained by the relative paucity of cell-specific promoters, but recent single-cell RNA-sequencing studies ( Taylor et al, 2021 ; Packer et al, 2019 ) have yielded novel cell-specific promoters for driving fluorescent proteins in neurons which previously lacked sparse-expressing genes.…”
Section: Introductionmentioning
confidence: 99%
“…This is strengthened by evidence of gap junctions in ultrastructural EM-based analyses in both invertebrates (Cook et al, 2019; Jarrell et al, 2012; White et al, 1986) and vertebrates (Smedowski et al, 2020; Anderson et al, 2011), as well as expression studies showing cell type-specific and tissue-specific spatial patterns of innexin and connexin genes (Bhattacharya et al, 2019). In addition, studies involving perturbations of innexins and connexins have shown diverse contributions of electrical synapses to neuronal function (Hendi et al, 2022; Bhattacharya et al, 2019; Hall, 2017; Song et al, 2016; Meng et al, 2016; Kawano et al, 2011; Bloomfield and Völgyi, 2009; Yeh et al, 2009; Chuang et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…For chemical synapses, these include reporters labeling pre- and post-synaptic proteins - such as SNB-1/VAMP, RAB-3, SYD-2/Liprin, CLA-1/Piccolo, GLR-1/AMPAR - fused with a fluorescent protein (Xuan et al, 2017; Mahoney et al, 2006; Yeh et al, 2005; Shen and Bargmann, 2003; Zhen and Jin, 1999; Nonet, 1999; Rongo et al, 1998; Jorgensen et al, 1995) and split-fluorophore transsynaptic technology such as GFP Reconstitution Across Synaptic Partners (GRASP) (Feinberg et al, 2008) and other variants (Feng et al, 2020; Feng et al, 2019), and Biotin Labeling of Intercellular Contacts (iBLINC) (Desbois et al, 2015) ( Figure 1A ). In the case of electrical synapses, innexins can be endogenously tagged with fluorescent proteins to visualize homomeric or heteromeric electrical synapses (Hendi et al, 2022; Gordon et al, 2020; Bhattacharya et al, 2019) ( Figure 1A ). These tools have been somewhat constrained by the relative paucity of cell-specific promoters, but recent single cell RNA-sequencing studies (Taylor et al 2021, Packer et al 2019) have yielded novel cell-specific promoters for driving fluorescent proteins in neurons which previously lacked sparse- expressing genes.…”
Section: Introductionmentioning
confidence: 99%
“…In C. elegans, loss of EGL-20/Wnt leads to axonal tiling defects in the DD5 and DD6 neurons, whereas presynaptic tiling is unaffected. However, when both EGL-20/Wnt and the gap junction protein UNC-9 are ablated, the synaptic tiling between these two neurons is lost [64].…”
Section: Wntsmentioning
confidence: 99%